Protective efficacy of six recombinant proteins as vaccine candidates against Echinococcus granulosus in dogs. - Guoqing Shao; Ruiqi Hua; Hongyu Song; Yanxin Chen; Xiaowei Zhu; Wei Hou; Shengqiong Li; Aiguo Yang; Guangyou Yang (Public Library of Science (PLoS), 2023)
Background Cystic echinococcosis (CE) is caused by the infection of Echinococcus granulosus sensu lato (E. granulosus s.l.), one of the most harmful zoonotic helminths worldwide. Infected dogs are the major source of CE transmission. While praziquantel-based deworming is a main measure employed to control dog infections, its efficacy is at times compromised by the persistent high rate of dog re-infection and the copious discharge of E. granulosus eggs into the environment. Therefore, the dog vaccine is a welcome development, as it offers a substantial reduction in the biomass of E. granulosus. This study aimed to use previous insights into E. granulosus functional genes to further assess the protective efficacy of six recombinant proteins in dogs using a two-time injection vaccination strategy. Methods We expressed and combined recombinant E. granulosus triosephosphate isomerase (rEgTIM) with annexin B3 (rEgANXB3), adenylate kinase 1 (rEgADK1) with Echinococcus protoscolex calcium binding protein 1 (rEgEPC1), and fatty acid-binding protein (rEgFABP) with paramyosin (rEgA31). Beagle dogs received two subcutaneous vaccinations mixed with Quil-A adjuvant, and subsequently orally challenged with protoscoleces two weeks after booster vaccination. All dogs were sacrificed for counting and measuring E. granulosus tapeworms at 28 days post-infection, and the level of serum IgG was detected by ELISA. Results Dogs vaccinated with rEgTIM&rEgANXB3, rEgADK1&rEgEPC1, and rEgFABP-EgA31 protein groups exhibited significant protectiveness, with a worm reduction rate of 71%, 57%, and 67%, respectively, compared to the control group (P < 0.05). Additionally, the vaccinated groups exhibited an inhibition of worm growth, as evidenced by a reduction in body length and width (P < 0.05). Furthermore, the level of IgG in the vaccinated dogs was significantly higher than that of the control dogs (P < 0.05). Conclusion These verified candidates may be promising vaccines for the prevention of E. granulosus infection in dogs following two injections. The rEgTIM&rEgANXB3 co-administrated vaccine underscored the potential for the highest protective efficacy and superior protection stability for controlling E. granulosus infections in dogs.